Public-private partnership (3Ps) in ensuring safe use of medicines: An Indian experience - Kalaiselvan, Vivekanandan; Shukla, Shatrunajay; Arora, Shubhang; Shrivastava, Tarani Prakash; Raghuvanshi, Rajeev Singh (Frontiers in Public Health, 2022)
Adverse drug reactions (ADRs) are major concerns to the public health. To monitor ADRs and ensure patients' safety, the Pharmacovigilance Programme of India (PvPI) has been established by the Government of India in 2010. The programme is intact with the Public-Private Partnership (3Ps) in pharmacovigilance for quality services, better management of human resources and risk minimization. The present work is aimed at assessing the 3Ps engagement, performance and tangible outcomes in PvPI and also mapping of resources. The study was carried out for the period of 2011 to 2021 by assessing the various benchmarking tools such as 3Ps categorization, utilization of ADRs reporting tools, trainings, and the Individual Case Safety Reports' (ICSRs) quantity, quality and transmission for regulatory intervention (RI). Under PvPI, Central or State Government medical institutions/hospitals and public health programmes constitute public partners while private medical institutions/hospitals, pharmaceutical companies, corporate hospitals and professional bodies account for private partners. We observed that public partners extensively used ADR reporting form and toll-free helpline number while private partners used mobile based app and emails/post as preferred tools for reporting ADRs. Contribution of public sector in training programmes organized, stakeholders trained and sharing of resource materials was way higher than the private sector. The study revealed that 55.1 and 44.9% ICSRs were received from public and private partners, respectively during the study period. The quality completeness of data received from public partners was found to be 0.92/1 as compared to 0.46/1 from the private partners. The ICSRs data transmitted for RI process from the public and private partners (till 2018) was found to be 79 and 21%, respectively. In terms of sharing of resources for training and capacity building, the public sector played a major role. The 3Ps in India are enabled to establish a robust system for medicines' safety surveillance; however a more focused approach is required in mapping the resources.